PENGARUH KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT DENGAN KECERDASAN SPIRITUAL SEBAGAI VARIABEL MODERATING (Studi persepsi Auditor pada Badan Pengawasan Keuangan dan Pembangunan Provinsi Jawa Tengah) - Ariati K, Kurnia; Rahardja, Rahardja (Diponegoro Journal of Accounting, 2014)
The aim of this research is to analyze perception study the effect of auditor competence to audit quality with spiritual intelligence as moderating variabel. As we know, in this era of globalization, the demands of society towards a quality auditor has increased over time. Therefore, in goverment organization, auditor of public sector has responsibility to determine that public resources has been use efficiently, effectively, economically and legally to create good governance and clean goverment. So that, auditor must consider to his/her competence to do audit process to produce a quality audit.The population in this research are all the internal auditors that worked at goverment organization. Sample of this research are internal auditors that worked at Badan Pengawasan Keuangan dan Pembangunan (BPKP) Provinsi Jawa Tengah. The analysis data used is SPSS program. Sampling method used is coviniece sampling. The Data used in this research is the primary data, that is done using the method of survey with questionnaire. Processing method used is moderating regression analysis.Based on the result of this research, the conclusion are: (1) auditor competence positively affect to audit quality and (2) spiritual intelligence doesn’t affect the relation between auditor competence and audit quality.